Advanced accounting - Hoyle, Joe Ben; Schaefer, Thomas F.; Doupnik, Timothy S. (New York, NY : McGraw-Hill Education, 2024)
"Overall-this edition of the text provides relevant and up-to-date accounting standards references to the Financial Accounting Standards Board (FASB) Accounting Standards Codification® (ASC). The approach used by Hoyle, Schaefer, and Doupnik allows students to think critically about accounting, just as they will in their careers and as they prepare for the CPA exam. Read on to understand how students will succeed as accounting majors and as future CPAs by using Advanced Accounting, 15e"--
Includes bibliographical references and index.
Keywords: Accounting